The Prognostic Value Of Serum Albumin In Acute Ischemic Stroke Patients (Latakia University Journal -Medical Sciences Series, 2022)
Background: Stroke is one of the most common causes of death and disability in the world. Determining mortality indicators is vital so that immediate remedial measures can be taken to improve outcome. Previous studies have identified factors such as stroke severity, stroke type, aging, impaired consciousness and hyperglycemia as indicators of mortality for acute stroke, but mortality remains high among patients hospitalized with acute stroke. Objectives: study of the relationship between low serum albumin during the first week of acute   ischemic stroke and residual rate and degree of functional disability according to (mRS) after 30 days. Methods and patients: Our study included 135 acute ischemic stroke patients and followed up for one month in terms of mortality and functional outcome. Albumin levels were determined in the first week of admission. We also performed a comprehensive neurological examination and determined the severity of stroke according to NIHSS. Brain CT scan was also performed. Results Patients with poor prognosis (mRS≥4) had significantly low albumin levels ​​than patients with good prognosis (mRS≤3)(p-value